2016
DOI: 10.1007/s10265-016-0819-y
|View full text |Cite
|
Sign up to set email alerts
|

A pqr2 mutant encodes a defective polyamine transporter and is negatively affected by ABA for paraquat resistance in Arabidopsis thaliana

Abstract: Despite the paraquat-resistant mutants that have been reported in plants, this study identified a novel A. thaliana mutant (pqr2) from an XVE inducible activation library based on its resistance to 2 μM paraquat. The pqr2 mutant exhibited a termination mutation in the exon of AT1G31830/PAR1/PQR2, encoded a polyamine uptake transporter AtPUT2/PAR1/PQR2. The PQR2 mutation could largely reduce superoxide accumulation and cell death in the pqr2 plants under paraquat treatment. Moreover, compared with wild type, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…PUT2 encodes an amino acid permease family protein and put2 mutants were reported to display resistance to paraquat (PQ), a methyl viologen widely used as a herbicide [24,25]. We found that put2-1 mutants were resistant to PQ, indicating that PUT2 activity is defective in put2-1 mutants (S2A Fig).…”
Section: Resultsmentioning
confidence: 95%
“…PUT2 encodes an amino acid permease family protein and put2 mutants were reported to display resistance to paraquat (PQ), a methyl viologen widely used as a herbicide [24,25]. We found that put2-1 mutants were resistant to PQ, indicating that PUT2 activity is defective in put2-1 mutants (S2A Fig).…”
Section: Resultsmentioning
confidence: 95%
“…Putrescine has a well-documented role in oxidative and abiotic stress tolerance, including drought stress [27]. With regard to PQ-induced oxidative stress, it has been suggested that putrescine competes with PQ for the polyamine transport system, thereby reducing the uptake of PQ [28]. This notion is supported by the discovery that natural variation in the polyamine transporter RMV1 (resistant to methyl viologen 1) determines PQ tolerance in Arabidopsis [29].…”
Section: Discussionmentioning
confidence: 99%
“…The LATs in human function as heteromeric exchangers of large neutral amino acids at 1:1 stoichiometry [4][5][6]10]. However, the Arabidopsis LATs have been demonstrated to have roles in mediating the transport of a range of substrates including amino acid, polyamine, paraquat, and thiamine [11][12][13][14][15][16][17]. The LAT5 was previously studied for its role in developmental responses, such as flowering and senescence, where it was called PUT5 under the assumption that it is a polyamine uptake transporter [18].…”
Section: Introductionmentioning
confidence: 99%